2020
DOI: 10.1002/med.21727
|View full text |Cite
|
Sign up to set email alerts
|

Reinvigorating exhausted CD8+ cytotoxic T lymphocytes in the tumor microenvironment and current strategies in cancer immunotherapy

Abstract: Immunotherapy has revolutionized the treatment of cancer in recent years and achieved overall success and long‐term clinical benefit in patients with a wide variety of cancer types. However, there is still a large proportion of patients exhibiting limited or no responses to immunotherapeutic strategy, some of which were even observed with hyperprogressive disease. One major obstacle restricting the efficacy is that tumor‐reactive CD8+ T cells, which are central for tumor control, undergo exhaustion, and lose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 371 publications
(930 reference statements)
0
60
0
Order By: Relevance
“…In the present study, the impressive findings were that memory T cell markers (central ~ effector memory), such as PD-1, CD27 and ICOS, were selected as prognostic factors. In addition to effector-activated CTLs and NK cells, memory marker + T cells should be considered crucial factors because i) PD-1 + T cells can achieve a good balance between good and poor responses by immune checkpoint blockade ( 27 ), and ii) effector memory T cells that proliferate by the stimulation of antigen-presenting cells, can be differentiated into activated effector CTLs ( 34 ). Another important observation was that T cell exhaustion marker genes such as HAVCR22 (TIM3) and TIGIT were included as prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the impressive findings were that memory T cell markers (central ~ effector memory), such as PD-1, CD27 and ICOS, were selected as prognostic factors. In addition to effector-activated CTLs and NK cells, memory marker + T cells should be considered crucial factors because i) PD-1 + T cells can achieve a good balance between good and poor responses by immune checkpoint blockade ( 27 ), and ii) effector memory T cells that proliferate by the stimulation of antigen-presenting cells, can be differentiated into activated effector CTLs ( 34 ). Another important observation was that T cell exhaustion marker genes such as HAVCR22 (TIM3) and TIGIT were included as prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in genome analysis technologies such as NGSand single-cell RNA sequencing, probable immunological factors belonging to the TME and associated with prognosis have been more intensively, specifically and accurately investigated (24)(25)(26). Beyond the already-known TME factors that might be responsible for the efficacy of cancer immunotherapy, such as positive PD-L1 expression, a high mutational burden and an advanced TIL status, more specific and dynamic biomarkers associated with the immune response have been reported (27)(28)(29). Recently, Kumagai et al demonstrated using cytometry by time of flight (CyTOF) analysis based on single-cell RNA-seq that a balance between Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD8 + T cells or so‐called CTLs are the most powerful effector cells that provide a backbone of successful immunotherapy (Raskov et al, 2021). The activity of CTLs can be enhanced to establish long‐lasting anticancer responses (Hossain et al, 2021). Macrophages constitute a large population of cells within tumors and their presence is associated generally with a weak prognosis.…”
Section: Cells and Signaling Of The Tme And The Characteristics Of An Abnormal Stromal Bed In A Tumormentioning
confidence: 99%
“…However, after prolonged antigen exposure, activated T-cells become hyporesponsive and with limited proliferative potential. Hence, T-cell exhaustion may protect tissues from potentially harmful effects of effector CD8 + T-cells 18 .…”
Section: Characteristics and Development Of Exhausted T-cellsmentioning
confidence: 99%